Preferência alimentar de adultos de Diabrotica speciosa (Ger.) (Coleoptera: Chrysomelidae) por genótipos de feijoeiro - Paron, Maria J. F. de O. [UNESP] (2001)
Tests were carried out to evaluate resistance of common bean (Phaseolus vulgaris L.) to Diabrotica speciosa (Ger.) with the genotypes Goiano Precoce, Jalo Precoce, PR 95105146, PR 95105142 (Andean domestication center, AN), Emgopa 201 Ouro and IAPAR 57 (Middle American domestication center, MA). The experiments were conducted in 1998 and 1999, at the farm of UNESP-FCAV, Jaboticabal, SP, Brazil. The genotypes were planted in pots and 20 day-old leaflets were collected and foliar disks were cut of for the test. Two trials, a no-choice test and a free-choice test, were set up in BOD. In free-choice test, two disks of each genotype were kept in a 140-mm-diameter petri dish (total of 12 disks), where 12 adults were confined. In no-choice test, two disks of one genotype and two insects were placed in a 60-mm-diameter petri dish. A field experiment was conducted when 400 adults of D. speciosa were released. Fifteen leaflets per plot were collected 30 days after planting and the leaf area consumption was evaluated. A no-choice experiment was carried out with 20 day-old genotypes protected in individual cages and infested by 10 adults, for 72h. The MA genotypes were the most preferred on feeding tests conducted at BOD, field and individual cages, while the AN genotypes were less eaten.